Viabilidade técnico-econômica da produção de biodiesel via rota alcalina e supercrítica baseadas em óleo residual - Lima, Auceliane André da Silva (2013)
The simulation of three processes for biodiesel production has been developed: transesterified refined oil (P-01); transesterified residual oil pretreated (P-02) and finally the residual oil supercritical transesterification (P-03 ) from commercial software Hysys ® 7.3, using the NRTL thermodynamic model. The analysis of the total capital invested was performed by individual factors Guthrie and percentage method provided in Peters et al., (1991). The total invested capital obtained by the method of single factor Guthrie was $7, $8.2 and $10 million, for the processes P-01, P-02 and P-03, respectively. In general, the total cost of annual production of biodiesel was performed taking into account the direct production costs, indirect costs, fixed costs, overheads and depreciation. The cost of the plant P-01 was verified for companies that pay the general rate, as well as those that have the social fuel seal, considering the exemption of 69 and 100% of PIS / COFINS. Profitability ratios used to evaluate the processes were the return on investment and payback period of the investment. Indices that take into account the value of money over time as the NPV (net present value) and internal rate of return (IRR) were also used to determine the project economically more profitable. Analysis of economic indicators shows that the supercritical transesterification unit is the most profitable of the three (return on investment of 36%, payback period equal to 1.59 years, NPV of $9.7 million and TIR equal to 33%). The second best investment with a 20% return was seen in the plant P-02. All economic indicator evaluated were negative for the unit P-01. The cost of annual biodiesel production facilities by P-01, P-02 and P-03 were $1.79/kg, $0.9/kg and $0.91/kg respectively. The sensitivity analysis showed that the most influential variables in the composition of investment return are the price of oil, biodiesel and glycerol. Finally, there was the effect of the variation of the acquisition costs of these components (between +50 and -50%), in the economic indicators (ROI, NPV and IRR).